WASP-128b: a transiting brown dwarf in the dynamical-tide regime. Issue 4 (14th September 2018) - Hodžić, Vedad; Triaud, Amaury H M J; Anderson, David R; Bouchy, François; Cameron, Andrew Collier; Delrez, Laetitia; Gillon, Michaël; Hellier, Coel; Jehin, Emmanuël; Lendl, Monika; Maxted, Pierre F L; Pepe, Francesco; et al.
ABSTRACT: Massive companions in close orbits around G dwarfs are thought to undergo rapid orbital decay due to runaway tidal dissipation. We report here the discovery of WASP-128b, a brown dwarf discovered by the WASP survey transiting a G0V host on a 2.2 d orbit, where the measured stellar rotation rate places the companion in a regime where tidal interaction is dominated by dynamical tides. Under the assumption of dynamical equilibrium, we derive a value of the stellar tidal quality factor Q_^′ = 6.96 ± 0.19 . A combined analysis of ground-based photometry and high-resolution spectroscopy reveals a mass and radius of the host, M_= 1.16± 0.04 M_, R_= 1.16± 0.02 R_, and for the companion, M_b = 37.5± 0.8 M_J, R_b = 0.94± 0.02 R_J, placing WASP-128b in the driest parts of the brown dwarf desert, and suggesting a mild inflation for its age. We estimate a remaining lifetime for WASP-128b similar to that of some ultra-short period massive hot Jupiters, and note it may be a propitious candidate for measuring orbital decay and testing tidal theories.